Identification of Potential Gene Regulatory Pathways Affecting the Ratio of Four-Seed Pod in Soybean - Fang, Ting; Bai, Yiwei; Huang, Wenxuan; Wu, Yueying; Yuan, Zhihui; Luan, Xiaoyan; Liu, Xinlei; Sun, Lianjun (Frontiers in Genetics, 2021)
The number of four-seed pod is one of the most important agronomic traits affected by gene and environment that can potentially improve soybean (Glycine max) yield. However, the gene regulatory network that affects the ratio of four-seed pod is yet unclear. Here, we performed bulked segregant RNA sequencing (BSR-seq) on a series of recombinant inbred lines (RILs) derived from hybrid progenies between a high ratio of four-seed pod cultivar Heinong 48 (HN48) and a low ratio of four-seed pod cultivar Henong 64 (HN64). Two tissues at flower bud stage and young pod stage, R1 and R3, were analyzed under the ratios of four-seed pod less than 10% and greater than 30%, respectively. To identify the potential gene regulation pathways associated with the ratio of soybean four-seed pod, we performed differentially expressed analysis on the four bulked groups. A differentially expressed gene (DEG) encoding a photosystem Ⅱ 5 kD protein had the function of participating in the energy conversion of photosynthesis. In addition, 79 common DEGs were identified at different developmental stages and under different ratios of four-seed pod. Among them, four genes encoding calcium-binding proteins and a WRKY transcription factor were enriched in the plant-pathogen interaction pathway and they showed a high level of expression in roots. Moreover, ten DEGs were identified in the reported quantitative trait locus (QTL) interval of four-seed pod, and two of them were significantly enriched in the pentose and glucuronate interconversions pathway. These findings provide basic insights into the understanding of the underlying gene regulatory network affected by specific environment and lay the foundation for identifying the targets that affects the ratio of four-seed pod in soybean.